2016
DOI: 10.1177/1049909116629134
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Fatigue Correlates With Higher Fatigue Scores Before Treatment

Abstract: We conclude that fatigue induced by chemotherapy is common and consistently associated with higher fatigue scores before treatment. Screening for fatigue before chemotherapy may help to identify patients who are prone to develop CIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…One study showed that MNA-score was predictive for fatigue evaluated by the Chalder Fatigue Scale (mean value at follow-up 26.8 ± 4.8; correlation coefficient r = − 0.52, p = 0.01) but not by the Brief Fatigue Inventory (mean value at follow-up 22.4 ± 23.7; correlation coefficient and p-value not reported) in chemotherapy-treated patients with various types of cancer and a mean age of 53 years [40].…”
Section: Other Outcomesmentioning
confidence: 89%
See 3 more Smart Citations
“…One study showed that MNA-score was predictive for fatigue evaluated by the Chalder Fatigue Scale (mean value at follow-up 26.8 ± 4.8; correlation coefficient r = − 0.52, p = 0.01) but not by the Brief Fatigue Inventory (mean value at follow-up 22.4 ± 23.7; correlation coefficient and p-value not reported) in chemotherapy-treated patients with various types of cancer and a mean age of 53 years [40].…”
Section: Other Outcomesmentioning
confidence: 89%
“…In 8 studies [40, 52-54, 56, 58, 69, 87] also patients < 65 years were included. In 3 of these studies [40,53,58] mean age was 65 years or lower.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the perception and evaluation of external events create variability in ANS and HPA activity levels, resulting in variable levels of perceived stress [3] that may influence inter-individual variability in fatigue severity. While higher levels of perceived stress were associated with greater fatigue severity [8][9][10][11][12][13][14][15], the majority of these studies were cross-sectional and evaluated only women with breast cancer [8][9][10][13][14][15].…”
Section: Introductionmentioning
confidence: 99%